Noisy but useful - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Gardening with Guineas - A Step by Step Guide to Raising Guinea Fowl on a Small Scale J S Ferguson. 1999. 131 pp. ISBN 0 7392 0250 2 US$ 14.95 E 17.50 Contact the distributor for the price of mail. FFE MEDIA PO Box 804 Waynesville, OH 45068-08